Process optimization for ethanol production from photoperiod-sensitive sorghum: Focus on cellulose conversion - Xu, Feng; Theerarattananoon, Karnnalin; Wu, Xiaorong; Pena, Leidy; Shi, Yong-Cheng; Staggenborg, Scott A.; Wang, Donghai (My University, 2011)
Photoperiod-sensitive sorghum, as a competitive biomass for ethanol production, was investigated to develop an integrated process for improving ethanol yield. Response surface methodology was employed to study the relationship between pretreatment variables (including temperature, sulfuric acid concentration, and reaction time) and cellulose recovery, as well as efficiency of enzymatic hydrolysis (EEH) in the solid part. Recovery yield decreased and EEH increased as the pretreatment temperature, acidic concentration, and reaction time increased. A model was successfully developed to predict total glucose yield with a maximum value of 82.2%. Conditions of co-fermentation were also optimized, and the optimal ethanol yield was obtained with constant-temperature simultaneous saccharification and fermentation at 38°C. Acetate buffer at a concentration of 50 mM was found helpful for increasing efficiency of enzymatic hydrolysis as well as ethanol yield. The maximum ethanol yield was 0.21 g ethanol per dry mass at the conditions of 38°C, 0.05 g yeast/L, and 50 mM acetate buffer. A complete cellulose balance was provided for the whole process.
Keywords: Photoperiod-sensitive sorghum; Ethanol; Response surface methodology; Sulfuric acid pretreatment; Fermentation